2020
DOI: 10.1186/s41205-020-00070-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of 3D additive manufacturing technology in autogenous dental transplantation

Abstract: Background In medicine and dentistry, 3D technology allows the virtual planning and printing of surgical replicas of anatomical structures that can facilitate certain transplant procedures. In dentistry, 3D technology is useful in autogenous tooth transplantation. Case presentation We present a clinical case of an ectopic mandibular second premolar, describing the preoperative planning with dental replicas and the autotransplantation surgery. 3D prints of the surgical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The shape and housing device manufactured, using 3D printing, conformed to the ergonomic design, and it was convenient for one-handed handheld operation. 3D printing new medical devices can be used in several departments, such as anesthesia, orthopedics, dental, and neurosurgery (Cahuana-Bartra et al, 2020 ; Faldini et al, 2020 ; Lan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The shape and housing device manufactured, using 3D printing, conformed to the ergonomic design, and it was convenient for one-handed handheld operation. 3D printing new medical devices can be used in several departments, such as anesthesia, orthopedics, dental, and neurosurgery (Cahuana-Bartra et al, 2020 ; Faldini et al, 2020 ; Lan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, wherever possible, the donor tooth's extraoral handling time should be kept to a minimum, as it has a negative impact on the tooth's viability. 10,11 To minimise damage to the donor tooth, helical CT/cone beam computed tomography is used in tandem with computer-aided rapid prototyping, which the printing of dental replicas for use as guides during surgery, thereby minimising extra-oral time and limiting possible damage to the donor tooth's periodontal tissue. All of this promotes the formation of a new recipient socket, so eliminating dangers to the donor tooth and, more broadly, aiding in the standardisation of the technique.…”
Section: D Printing Application In Autotransplantationmentioning
confidence: 99%
“…53 In cases with palatal clefts involving complex decisions, like osseous grafts or the need to preserve crucial anatomic structures, CBCT may be required. Combining low mAs (16) and kVp (70) with a small voxel size (180 μm) enables the association of a low effective dose with high image quality. 54 More recently, the possibility of using magnetic resonance imaging (MRI) as a feasible tool for orthodontic treatment planning without radiation exposure has been described, by transforming the acquired data into lateral cephalograms, allowing reliable measurements, similar to those applied in orthodontics routine or related disciplines, such as orthognathic surgery, despite the need for specific post-processing software and an experienced user.…”
Section: Introductionmentioning
confidence: 99%
“…Despite not being focused on M2P agenesis, a study by Cahuana-Bartra et al revealed that patients with hypodontia showed satisfaction with resinbonded bridges over a 7-year observation period, with an 88% success. 70 Regarding treatment options, data from 42 studies published in the years 1980-2015 presented a mean survival of 95.3%, 94.4%, 89.6%, and 60.2% for implants, autotransplants, retained primary teeth, and conventional prostheses, respectively. 64 Meanwhile, the mean satisfaction rates for the type of treatment, i.e., for implants, conventional prostheses, autotransplants, and orthodontic space closure, 93.4%, 76.6%, 72.0%, and 65.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%